If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -1 = -10 Reorder the terms: -1 + 3x = -10 Solving -1 + 3x = -10 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + 3x = -10 + 1 Combine like terms: -1 + 1 = 0 0 + 3x = -10 + 1 3x = -10 + 1 Combine like terms: -10 + 1 = -9 3x = -9 Divide each side by '3'. x = -3 Simplifying x = -3
| -21b-43=b-153 | | 46.50=15+5.25w | | 7k-8+3k+14=52 | | x^2-5a^2-4ax=0 | | 50=-50+w | | 7x+3=4(x+2) | | 50=50+w | | -7(1-4x)=13(3x-9) | | (3x+5)ln=4 | | 15-h=5-6 | | -14x-6-2x=-8x-14 | | X-5.625=-6.3+5 | | 2x+14=x | | a-584=-22a-9 | | 8x-7=7x+12 | | 7(t-4)+5t=6(2t+3)-9 | | -10y+18=-31(54-7)-8 | | a-589=-22a-9 | | X-17+(-5)=-23 | | 14x=30+20x | | ln(3x+5)=4 | | t-54=2-9 | | 4x^2+4x=-36 | | 3x=21+12 | | 2x-5=34 | | 8x=600 | | 2x=5y-10 | | 2-11=12-d | | 5x+3(x-5)=6x+2x-15 | | 5x+160=70 | | 600x=8 | | 4.5=10x |